Profitabilitas Memediasi Likuiditas dan Leverage Terhadap Kebijakan Dividen Perusahaan Manufaktur Sektor Industri Barang dan Konsumsi - Zuni Rochmawati; Yuniningsih Yuniningsih (Universitas Mataram, 2022)
The reason for this research is to know the role of profitability as an intervening variable in influencing liquidity and leverage on dividend policy. The population used is manufacturing companies in the industrial sector of goods and consumption listed on the Indonesia Stock Exchange in the period 2017 – 2020. The method used in determining the sample uses the purposive sampling method. It was obtained that 20 companies were observed for 4 years so the total observed data was 80. Using data analysis techniques, namely path analysis, outlier test, classical assumption test, hypothesis testing and , detection of mediating effect (Sobel test) with the help of tools SPSS data analysis software. The results of the study explain that liquidity and leverage have a positive and significant effect on profitability. Liquidity and Leverage have no effect on dividend policy, while profitability has a positive and significant effect on dividend policy. Profitability is able to mediate the effect of the relationship between Liquidity and Leverage on Dividend Policy through an indirect effect that is greater than the direct effect and is also evidenced by using the Sobel Test.